Effect of Switching to a High-Deductible Health Plan on Use of Chronic Medications - Reiss, Sheila K (Blackwell Science Inc, 2011)
OBJECTIVE: To examine whether high-deductible health plans (HDHPs) that exempt prescription drugs from full cost sharing preserve medication use for major chronic illness, compared with traditional HMOs with similar drug cost sharing. DATA SOURCES/STUDY SETTING: We examined 2001–2008 pharmacy claims data of 3,348 continuously enrolled adults in a Massachusetts health plan for 9 months before and 24 months after an employer-mandated switch from a traditional HMO plan to a HDHP, compared with 20,534 contemporaneous matched HMO members. Both study groups faced similar three-tiered drug copayments. We calculated daily medication availability for all prescription drugs and four chronic medication classes: hypoglycemics, lipid-lowering agents, antihypertensives, and chronic obstructive pulmonary disease (COPD)/asthma controllers. STUDY DESIGN: Interrupted time-series with comparison group study design examining monthly level and trend changes in prescription drug utilization. PRINCIPAL FINDINGS: The HDHP and control groups had comparable changes in the level and trend of all drugs after the index date; we detected similar patterns in the use of lipid-lowering agents, antihypertensives, and COPD/asthma controllers. Some evidence suggested a small relative decline in hypoglycemic use among diabetic patients in HDHPs. CONCLUSIONS: Switching to an HDHP that included modest drug copayments did not change medication availability or reduce use of essential medications for three common chronic illnesses.